A QUESTÃO DO VALOR NA CRÍTICA E NA PRODUÇÃO CULTURAL CONTEMPORÂNEA - Valterlei Borges de Araujo (Travessias, 2012)
This article addresses the importance of rescuing the question of value in contemporary cultural criticism, taking as a basis for discussions the music conveyed by the new media generated by the Internet. In developing the exhibition, we will also talk about some questions relating to Cultural Studies and touch on some subjects related to developments in the digitization of music, however, always thinking about the question of value, especially in contemporary times.